Using Reverse Engineering to Handle Malware - Sánchez Venegas, Carlos Andrés; Aguado Bedoya, Camilo; Díaz López, Daniel Orlando; García Ruíz, Juan Carlos Camilo (Ingeniería Solidaria, 2019)
Introduction: This paper is a product of the research Project “Cyber Security Architecture for Incident Management” developed in the Colombian School of Engineering Julio Garavito in the year 2018.Objetive: Reverse engineering involves deconstructing and extracting knowledge about objects. The use of reverse engineering in malware analysis is extremely useful in understanding the functionalities and purposes of a suspicious sample.Methods: This paper makes use of Radare which is one of the most popular open source tools for reverse engineering, with the aim of dealing with malware.Results: A use case related to hacking of anti-sandbox malware is presented, in such a way that it is possible to analyze the behavior of the sample using a sandbox. Additionally, another use case is presented, where an in-depth analysis of a malicious Android application aimed to the audience of a popular event (FIFA World Cup 2018) is developed, making it possible to demonstrate the relevance of reverse engineering techniques in end-user protection strategies. Conclusions: This paper shows how the results of a reverse engineering process can be integrated with Yara rules, allowing for the detection of malware on the fly, and it also shows an alternative to automatically generating Yara rules through the yarGen generator.Originality: Use of Open Source reversing solutions by Colombian Law Enforcement Agencies has not been discussed previously, making this paper a notable element toward the modernization of the Army.Limitation: Different approaches and perspectives about the limitations in the use of reverse engineering by Law Enforcement Agencies are also shared.
Keywords: Reverse engineering; Radare; Sandboxing; Yara rules; Malware analysis